Serum Zinc Concentrations in the US Population Are Related to Sex, Age, and Time of Blood Draw but Not Dietary or Supplemental Zinc. Issue 8 (27th June 2018) - Hennigar, Stephen R; Lieberman, Harris R; Fulgoni, Victor L; McClung, James P
Abstract: Background: Serum zinc concentration is used to assess the zinc status of populations. Cutoffs for serum zinc were developed on the basis of data from the second NHANES (1976–1980). Objective: The objective of this study was to evaluate serum zinc concentrations in the US population and to determine factors affecting serum zinc with the use of NHANES 2011–2014. Methods: Serum zinc was determined in males and females aged ≥6 y with the use of NHANES 2011–2014 ( n  = 4347). Dietary zinc intake was determined, and factors affecting serum zinc were identified with the use of regression models adjusting for sex, age, fasting status, and time of blood draw. ORs were calculated to identify factors associated with the risk of being below the serum zinc cutoff, and the prevalence of low serum zinc in the US was calculated. P  < 0.01 was considered significant. Results: Mean ± SE serum zinc concentrations in males and females were 84.9 ± 0.8 and 80.6 ± 0.6 μg/dL, respectively ( P  < 0.0001). Regression models with serum zinc as the dependent variable indicated that afternoon and evening blood draws (β = –9.7 and –15.3; P  < 0.0001) were negatively associated with serum zinc concentrations and serum albumin (β = 16.1; P  < 0.0001) and hemoglobin (β = 1.0; P = 0.0048) were positively associated with serum zinc concentrations. Hypoalbuminemia (OR = 11.2; 99% CI: 3.4, 37.3), anemia in females (OR: 3.4; 99% CI: 1.7, 6.9), and pregnancy (OR: 9.6; 99% CI: 2.9, 31.9) increased the odds of being below the serum zinc cutoff ( P  < 0.0001 for all). Zinc from diet or supplements did not affect serum zinc ( P  > 0.01). Approximately 3.8% of children (<10 y), 8.6% of males (≥10 y), and 8.2% of females (≥10 y) were below the serum zinc cutoff. Conclusions: Factors such as sex, age, and time of blood draw should be considered when using serum zinc concentration to determine the zinc status of a population. Caution is advised when interpreting serum zinc concentration in populations with a high prevalence of hypoalbuminemia or anemia. This trial was registered at http://www.isrctn.com as ISRCTN96013840.